Vitamin D3 formation in milk by ultraviolet treatment—Novel insights into a rediscovered process - Jaayke L. Fiege; Alexandra Ohrt; Stefan Hebig; Katrin Schrader; Volker Gräf; Dierk Martin; Ronald Maul; Mario Stahl (Journal of Dairy Science)
ABSTRACT: Vitamin D3 is essential for several functions in the human body and the demand is usually covered by natural reactions in skin with UV radiation delivered by the sun. But living beyond a latitude of 35° can lead to a lack of sufficient exposure to the deciding wavelength. Here, many countries fortify their milk prophylactically with artificial vitamin D3. However, the precursor molecule of vitamin D3 (7-deydrocholesterol) is already naturally located in the milk fat globule membrane. Thus, this study deals with the transformation of the naturally occurring 7-dehydrocholesterol into vitamin D3 through UV treatment of the milk—a mechanism that was observed a century ago only indirectly. Different parameters such as temperature (10–50°C), fluid flow regimen (turbulent vs. laminar thin film, i.e., 0.6 mm), and wavelength (254, 280, and 313 nm) were investigated in this study for their efficiencies. The UV dose of each experiment was measured, with chemical actinometry delivering the actual applied dose reaching the milk. Thus, the connection between applied UV dose and generated vitamin D3 content in the milk measured quantitively with liquid chromatography-MS/MS was evaluated here; neither of these measurements were possible a hundred years ago. The experimental results revealed that temperature generally promotes vitamin D3 formation at 254 nm. Furthermore, a turbulent flow is not as efficiently treated as a laminar thin film flow that is as narrow as 0.6 mm. As expected from absorbance spectra of the precursor molecule 7-dehydrocholesterol, 280 nm turned out to be the most efficient wavelength, followed by intermediate success through irradiation with 254 nm and almost no effect by 313 nm. Generally, it was shown that the vitamin D3 concentration of milk was easily increased by UV treatment with today's technologies and that adjustment of certain physical parameters have a distinct effect on the efficiency of the process.